In situ x-ray analysis of misfit strain and curvature of bent polytypic GaAs–InxGa1−xAs core–shell nanowires. (20th October 2021) - Al-Humaidi, Mahmoud; Feigl, Ludwig; Jakob, Julian; Schroth, Philipp; AlHassan, Ali; Davtyan, Arman; Herranz, Jesús; Anjum, Tasser; Novikov, Dmitri; Francoual, Sonia; Geelhaar, Lutz; Baumbach, Tilo; et al.
Abstract: Misfit strain in core–shell nanowires can be elastically released by nanowire bending in case of asymmetric shell growth around the nanowire core. In this work, we investigate the bending of GaAs nanowires during the asymmetric overgrowth by an In x Ga1− x As shell caused by avoiding substrate rotation. We observe that the nanowire bending direction depends on the nature of the substrate's oxide layer, demonstrated by Si substrates covered by native and thermal oxide layers. Further, we follow the bending evolution by time-resolved in situ x-ray diffraction measurements during the deposition of the asymmetric shell. The XRD measurements give insight into the temporal development of the strain as well as the bending evolution in the core–shell nanowire.